InFoDiTex: What we do and what we want - Karcher, Stefan; Nunn, Christopher Alexander (Interdisciplinary forum of digital textual sciences, 2018)
In the spring of 2016, two graduate students in theology sat together during a coffee break: One of them complained: “It is impossible to find the most suitable method to work with my digitized cor…